Optimization of the Ultrasonic Extraction Process of Kasumba Turate (Carthamus tinctorius Linn) Using the Response Surface Metodology (RSM) Technique - Zulfikar, Zulfikar; Hendrawati, Tri Yuni; Redjeki, Athiek Sri (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2024)
Kasumba turate (Carthamus tinctorius Linn) or safflower is a traditional medicine used by South Sulawesians. Polyphenol compounds and antioxidant activity are active components of kasumbu turate. This component can be obtained through extraction. The goal of this study was to find the best conditions for extracting kasumba turate with high total phenol levels and strong antioxidant activity, as well as encapsulating the resulting extract. The ultrasonic assisted extraction (UAE) method was used to extract Kasumba turate with methanol, and the Responses surface Methodology method was used to optimize the extraction. Behnken Box Variations in composition solutions of 50, 60, 70, 80, and 90%, as well as time variations of 20, 30, 40, 50, and 60 minutes. A solvent ratio of was used for sample extraction 1: 1 using Methanol solvent and water, determined which is the best result of this variable, and continued by analyzing is a test analysis with Spectrophotometry, DPPH, and the best results of the variable are analyzed using Spectofotometry to see the content of flavonoid compounds in Kasumba Turate Flowers.